The 2004 Constitution and Shariah: Examining Legal Tensions in Afghanistan - Faizan, Muhibullah; Binti Mohamad Amin, Noor Shuhadawati; Haji Mohammad, Mohammad Tahir Sabit (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract The 2004 Constitution of Afghanistan (2004 Afghan Constitution) was made based on the Bonn Agreement which required the Afghan government to establish an Afghan legal framework in collaboration with the international community. It led to the incorporation of different sources of law such as Shariah, the constitution, and international human rights standards without reconciling the contradictory concepts that undermined the position of the Aghan 2004 constitution due to its inconsistency with Shariah. With this problem in consideration, this study attempts to identify sources of law by focusing on the role of Shariah in case of conflict between constitutional provisions. It seeks to specify the supreme source of law by addressing the hierarchy of constitutional norms to pave the way for filling the legal gap. To achieve this objective, the research uses the doctrinal method of elaborating constitutional provisions to discover the supreme source of law. The researcher analyses the legal authority of the 2004 Afghan Constitution under constitutional provisions that introduce conflicting sources of law. In addition to this, the 2004 Afghan Constitution does not fully subject itself to Shariah while aligning law with Shariah. It provides a distinct meaning of constitution and law which resulted in weakening the position of Shariah compared to other sources of law. However, the 2004 Afghan constitution treats its provisions to be binding while providing provisions contrary to Shariah which is established under irrevocable provision. Hence, the constitutional gap might be filled by enacting a new constitution under the supremacy of Shariah.